The influence of workplace stressors on the risk of cardiovascular diseases among healthcare providers: a systematic review - Alhajaji, Raghad; Alfahmi, Manal Z.; Alshaikhi, Saleh Ahmed; Fairaq, Abdulmajeed Mohammed; Fudlaldeen Jan, Salman; Aljuaid, Sultan; AlFaifi, Mashael; Alaboud, Mashael S.; Khojah, Imad Mohammed; Alkofide, Hadeel; Al Sulaiman, Khalid (Frontiers in Psychiatry, 2025)
BackgroundCardiovascular diseases (CVDs) are a leading cause of death worldwide. Healthcare workers are at increased risk due to workplace stressors such as long hours, shift work, and high job demands, which may worsen both modifiable and non-modifiable CVD risk factors. This systematic review examines the impact of these workplace stressors on the risk for CVD among healthcare providers.MethodsWe conducted a systematic review of observational studies from inception to January 2024, following PRISMA guidelines. We searched databases including PubMed, Embase, Scopus, Web of Science, and PsycINFO using keywords related to workplace stressors and CVDs among healthcare professionals. The quality of the studies was assessed using the Newcastle-Ottawa Scale (NOS).ResultsOur review included 31 observational studies (15 cohort studies, 13 cross-sectional studies, and three case-control studies) with a total of 323,978 participants from 17 countries. The key stressors identified were long working hours, night shifts, and high job strain. Most studies reported significant associations between these stressors and increased risks of hypertension, ischemic heart disease, and cardiometabolic disorders. The quality of the studies ranged from fair to good, indicating a low risk of bias.ConclusionGrowing evidence suggests a strong correlation between workplace stressors and an increased risk of cardiovascular disease among healthcare workers. This leads to negative consequences that affect their performance and may extend to the quality of their patients’ care. Addressing these stressors through targeted interventions is crucial for protecting their health and improving patient care outcomes.